2004
DOI: 10.1242/jcs.00880
|View full text |Cite
|
Sign up to set email alerts
|

Swm1p subunit of the APC/cyclosome is required for activation of the daughter-specific gene expression program mediated by Ace2p during growth at high temperature inSaccharomyces cerevisiae

Abstract: SWM1 was originally identified for its role in the late steps of the sporulation process, being required for spore wall assembly. This protein, recently identified as one of the core subunits of the anaphase-promoting complex (APC) is also required to complete cell separation in vegetative cells during growth at high temperature. Mutants lacking SWM1 show a thermosensitive growth defect that is suppressed by osmotic support in the culture medium. At the restrictive temperature, swm1 mutants are unable to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 66 publications
4
28
0
Order By: Relevance
“…Protein abundance peaks at late anaphase and then diminishes as mitosis is completed. This timing would be consistent with Ace2p nuclear accumulation requiring activation of the anaphase-promoting complex (APC), which is a multisubunit E3 ubiquitin ligase (Harper et al, 2002;Peters, 2002), as seems to be the case in budding yeast (Ufano et al, 2004). In S. cerevisiae, cells with a mutant version of the APC component Swm1p, do not accumulate Ace2p in the daughter nucleus.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Protein abundance peaks at late anaphase and then diminishes as mitosis is completed. This timing would be consistent with Ace2p nuclear accumulation requiring activation of the anaphase-promoting complex (APC), which is a multisubunit E3 ubiquitin ligase (Harper et al, 2002;Peters, 2002), as seems to be the case in budding yeast (Ufano et al, 2004). In S. cerevisiae, cells with a mutant version of the APC component Swm1p, do not accumulate Ace2p in the daughter nucleus.…”
Section: Discussionsupporting
confidence: 62%
“…In S. cerevisiae, cells with a mutant version of the APC component Swm1p, do not accumulate Ace2p in the daughter nucleus. These mutant cells do not express genes under Ace2p control and exhibit mitotic exit and cell separation defects (Ufano et al, 2004). It remains to be determined, however, whether the APC affects S. pombe Ace2p.…”
Section: Discussionmentioning
confidence: 99%
“…It might be important that translocation of Ace2 occurs abruptly because nuclear Ace2 is unstable (29). While this paper was being revised, Ufano et al reported experiments showing that the cell separation phenotype stems from a defect in nuclear accumulation of Ace2 (42). The SWM1 deletion also reduced the activity of APC/C-Cdh1, causing a stabilization of Clb2 in G 1 -arrested cells.…”
Section: Discussionmentioning
confidence: 91%
“…However, suppression of the separation defect was not complete, indicating that Ace2p might be regulated by other mechanisms. Although we have ruled out the contribution of the SIN in controlling Ace2p function, it is possible that, by analogy with S. cerevisiae Ace2p, Cdk1p, or Orb6p (similar to S. cerevisiae Cbk1p) phosphorylation might be involved in its regulation (O'Conallain et al, 1999;Weiss et al, 2002;Nelson et al, 2003;Ufano et al, 2004). It is also possible that Sep1p not only regulates ace2 ϩ transcription, but also the activity or localization of Ace2p.…”
Section: Discussionmentioning
confidence: 97%